Scoping Review on Microplastic Pollution in Aquatic Species Across Indonesian Waters - Ashiba Marikar; Balázs Ádám (Science, Technology, and Education Care, 2026)
Microplastics (MP) pollution is an emerging environmental threat in aquatic ecosystems, with implications for both biodiversity and human health. As one of the world’s largest archipelagic nations and a top contributor to marine plastic waste, Indonesia faces significant challenges related to MP contamination in its waters. This scoping review aims to map existing evidence on MP pollution among aquatic species in Indonesian waters. A comprehensive search was conducted in the PubMed database between April and May 2025, guided by the Population-Concept-Context framework. The review followed the PRISMA-ScR guidelines. Studies were included if they addressed MP pollution in aquatic organisms in Indonesia and were published in English. Data were extracted systematically, covering study characteristics such as MP types, sizes, shapes, colors, polymer composition, and detection methods. A total of 13 eligible studies were included. These studies examined MP contamination in various aquatic organisms, including fish, bivalves, sea urchins, and sandfish across freshwater, coastal, and aquaculture environments. Predominant MP shapes were fibers, fragments, and films, with sizes ranging from <100 µm to 5000 µm. The most frequently detected polymers were polyethylene, polypropylene, polystyrene, and polyvinyl chloride. Black was the most common color of MP, followed by blue. Filter feeders and species near polluted areas showed higher MP loads. The diversity in MP color, size, and polymer composition reflects a mix of land- and marine-based pollution sources. Differences in detection and limited health-impact data highlight the need for more consistent, in-depth research, emphasizing standardized protocols and further studies assessing biological and health impacts. This review points out the widespread presence of MP in aquatic species consumed by humans, raising significant concerns for seafood safety and environmental health in Indonesia. These findings highlight the urgent need for standardized analytical protocols and strengthened regulatory measures to address MP pollution, positioning it as an emerging environmental health priority in Indonesia.